2009
DOI: 10.1097/aln.0b013e318191408c
|View full text |Cite
|
Sign up to set email alerts
|

CU-2010—A Novel Small Molecule Protease Inhibitor with Antifibrinolytic and Anticoagulant Properties

Abstract: Background:In cardiac surgery, the contact of blood with the artificial surfaces of the cardiopulmonary bypass results in activation of coagulation, fibrinolysis, and platelets, which is recognized as reason for increased bleeding tendency. Antifibrinolytics like tranexamic acid or the broad-spectrum protease inhibitor aprotinin attenuate this response. The marketing of aprotinin has been suspended after a recent clinical trial suggested increased risks associated with aprotinin. Moreover, aprotinin is a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 40 publications
3
55
0
Order By: Relevance
“…The molecule had been assed in in-vitro studies and demonstrated a high affinity to plasmin comparable to aprotinin and 10 times more potent than tranexamic acid [28]. The molecule also inhibited kallikrein and coagulation factors Xa and Xia.…”
Section: New Drugs In Clinical Developmentmentioning
confidence: 97%
“…The molecule had been assed in in-vitro studies and demonstrated a high affinity to plasmin comparable to aprotinin and 10 times more potent than tranexamic acid [28]. The molecule also inhibited kallikrein and coagulation factors Xa and Xia.…”
Section: New Drugs In Clinical Developmentmentioning
confidence: 97%
“…37,38 Similarly, other plasma kallikrein inhibitors have also shown to have antithrombotic properties in vitro or in animal models of venous and arterial thrombosis ( Table 1). [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] These studies provide strong evidence that although components of the plasma KKS are dispensable for normal hemostasis, they play a central role in pathological thrombus formation.…”
Section: Plasma Kallikrein: Synthesis Structure and Functionsmentioning
confidence: 98%
“…A relatively strong trypsin inhibition was still found for the phenylsulfonyl and cyclohexylsulfamoyl analogues 29 and 31, with K i values of 62 and 21 nM, respectively, which is in the same range as found for the reference compounds 2 and 3 ( Table 2). 25,27 The strong subnanomolar inhibitory potency of compounds 3, 29, and 31 suggested that plasmin should tolerate some P1 modifications, which lead to a generally reduced affinity against all trypsin-like serine proteases. Therefore, additional inhibitors with the longer piperazine-dipropionyl linker have been prepared, which provided slightly more potent inhibitors than the shorter piperazine-diacetyl linker.…”
Section: Synthesismentioning
confidence: 98%